2016
DOI: 10.1155/2016/9673054
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Sleep-Related Breathing Disorders in Middle East and UAE

Abstract: A pandemic of obesity is sweeping all across the globe and the Middle East region also does not remain untouched by this prevailing pandemic. In fact, as per WHO report, Kuwait has the second highest obesity prevalence followed closely by other Middle East (ME) countries, namely, Qatar, Saudi Arabia, and United Arab Emirates (UAE). Apart from direct medical, psychological, and quality of life related adverse effects of obesity, many indirect medical comorbidities, namely, obstructive sleep apnea (OSA), obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
1
14
0
1
Order By: Relevance
“…The majority of referrals for polysomnography were made by chest physicians, which may indicate a lack of awareness on the part of primary care physicians, who were responsible for <5% of referrals, but also of other concerned specialties such as cardiologists, endocrinologists and ENTs. A similar referral pattern has been observed in a previous study of sleep apnea in the Middle East region [18].…”
Section: Discussionsupporting
confidence: 88%
“…The majority of referrals for polysomnography were made by chest physicians, which may indicate a lack of awareness on the part of primary care physicians, who were responsible for <5% of referrals, but also of other concerned specialties such as cardiologists, endocrinologists and ENTs. A similar referral pattern has been observed in a previous study of sleep apnea in the Middle East region [18].…”
Section: Discussionsupporting
confidence: 88%
“…A review article exploring this topic found that studies were done in countries such as Dubai, United Arab Emirates found up to 22% of participants are at risk for OSA (Table 1). 41,42…”
Section: Differences In Ethnicitymentioning
confidence: 99%
“…In Asian population, a BMI greater than 23kg/m 2 is used to distinguish overweight status and greater than 28 kg/m 2 to denote obesity. Vats et al, 50 argue that obesity is a growing problem in the Middle East, but the scarcity of sleep centres limits data collection. 50 In a comparison of White Europeans to South Asians, White Europeans had greater rates of OSA due to greater rates of obesity and central adiposity in White Europeans.…”
Section: Prevalence and Screeningmentioning
confidence: 99%
“…Vats et al, 50 argue that obesity is a growing problem in the Middle East, but the scarcity of sleep centres limits data collection. 50 In a comparison of White Europeans to South Asians, White Europeans had greater rates of OSA due to greater rates of obesity and central adiposity in White Europeans. 51,52 In a study of Korean patients having polysomnography without a history of T2DM, those with the highest rate of T2DM or IFG(impaired fasting glucose) had a mean BMI of 27kg/m 2 .…”
Section: Prevalence and Screeningmentioning
confidence: 99%